2011
DOI: 10.1029/2011gl049785
|View full text |Cite
|
Sign up to set email alerts
|

The driving of baroclinic anomalies at different timescales

Abstract: This work investigates the internal variability of zonal‐mean baroclinicity over the Southern Hemisphere midlatitudes. The first two leading modes describe a meridional baroclinicity shift and a sharpening/broadening of baroclinicity, with the shift becoming more dominant at low frequency. The lifecycles of the baroclinic anomalies, estimated by means of lagged regression analysis, are qualitatively different depending on the frequency range. At high frequency, the zonal‐mean baroclinicity simply responds to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
4
13
0
Order By: Relevance
“…The role played by the low-phase-speed eddies in our model in maintaining the lower-level baroclinicity in the annular modes is consistent with the very recent observational study by Blanco-Fuentes and Zurita-Gotor (2011), in which they also found that the low-frequency eddies, in contrast to the synoptic eddies, contribute to the low-frequency latitudinal shift of the zonal flow baroclinicity along with the SAM. When the surface friction on baroclinic eddies is increased, the leading mode of the zonal wind variability can shift from a latitudinal fluctuation of the jet position to a pulsing of the jet intensity.…”
Section: Summary and Discussionsupporting
confidence: 91%
“…The role played by the low-phase-speed eddies in our model in maintaining the lower-level baroclinicity in the annular modes is consistent with the very recent observational study by Blanco-Fuentes and Zurita-Gotor (2011), in which they also found that the low-frequency eddies, in contrast to the synoptic eddies, contribute to the low-frequency latitudinal shift of the zonal flow baroclinicity along with the SAM. When the surface friction on baroclinic eddies is increased, the leading mode of the zonal wind variability can shift from a latitudinal fluctuation of the jet position to a pulsing of the jet intensity.…”
Section: Summary and Discussionsupporting
confidence: 91%
“…Following Blanco‐Fuentes and Zurita‐Gotor [], we investigate the driving of low‐frequency baroclinicity variability by analyzing the relations between baroclinicity and its forcing terms in the vertically integrated thermodynamic equation (vertical integrals are denoted with angle brackets ⟨⟩): ⟨⟩θytrue¯t=prefix−aφ()1normalcosφ⟨⟩vθtrue¯normalcosφaφaφ⟨⟩trueω¯Θp+other terms …”
Section: Resultssupporting
confidence: 88%
“…We group all other terms together with the diabatic heating and any discretization errors into a residue. Blanco‐Fuentes and Zurita‐Gotor [] project spatially all the above terms on the leading EOF of baroclinicity variability, which has dipolar structure and is highly correlated with SAM. Here we project instead on the baroclinicity pattern congruent with the heat flux variability, obtained regressing ⟨⟩θytrue¯(),yt on BAM.…”
Section: Resultssupporting
confidence: 88%
“…They found evidence of baroclinicity driving the barotropic flow and very large coherence between the eddy heat and momentum fluxes at low frequency, with the momentum fluxes leading the variability, see Figure e. The covariability between the barotropic and baroclinic components of the wind is also a robust result in observations (Blanco‐Fuentes & Zurita‐Gotor, ) and comprehensive climate models. In Figure d the large correlation between the long‐lag decay rates of (barotropic) jet anomalies and baroclinicity is shown for a selection of CMIP5 models, so that models with more persistent jet variability also tend to have more persistent baroclinicity.…”
Section: The Midlatitude Circulationmentioning
confidence: 73%